2012
DOI: 10.25011/cim.v35i3.16588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleeping energy expenditure using the SenseWear Armband in patients with overt and subclinical hypothyroidism

Abstract: Purpose: e aim of the present study was to evaluate the average sleeping energy expenditure (EE) levels using the SenseWear Armband (SWA) in patients with overt and subclinical hypothyroidism.Methods: Sixty patients with hypothyroidism and 30 healthy individuals were recruited for the study. Hypothyroid patients were divided into two groups: group 1 (n = 30) consisted of patients with overt hypothyroidism and group 2 (n = 30) consisted of patients with subclinical hypothyroidism. Lastly, group 3 (n = 30) consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Al-Adsani et al [8] observed that slight changes in thyroid hormone levels affected the RMR but not the TEG. However, Ulas et al [19] showed that energy expenditure during sleep was similar between hypothyroid and healthy subjects. Our studies have clearly showed that hypothyroidism associated with reduction in energy expenditure occurs not only in the case of RMR but also in the case of reducing TEG.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Adsani et al [8] observed that slight changes in thyroid hormone levels affected the RMR but not the TEG. However, Ulas et al [19] showed that energy expenditure during sleep was similar between hypothyroid and healthy subjects. Our studies have clearly showed that hypothyroidism associated with reduction in energy expenditure occurs not only in the case of RMR but also in the case of reducing TEG.…”
Section: Discussionmentioning
confidence: 99%
“…Each moment of our day is spent in one of three basic activities: PA, SB and sleep. 7 Each of these behaviours is mutually exclusive, has different energy expenditures from each other 10 , 23 , 24 and is physiologically distinct phenomena – both in the periphery and the brain. 25 - 31 …”
Section: What Are Time-use Activity Behaviours?mentioning
confidence: 99%
“…These considerations include ( 1 Each moment of our day is spent in one of three basic activities: PA, SB and sleep. 7 Each of these behaviours is mutually exclusive, has different energy expenditures from each other 10,23,24 and is physiologically distinct phenomenaboth in the periphery and the brain. [25][26][27][28][29][30][31] There are at least four separate terms used to collectively describe PA, SB and sleep.…”
Section: Introductionmentioning
confidence: 99%
“…A small study comparing subjects with frankly hypothyroid and subclinical hypothyroid and healthy control subjects did not observe any difference in their sleeping EE when measured by accelerometers and metabolic equivalent of task (MET) at baseline and after achieving euthyroidism [47]. This is not surprising because the frank hypokinesia is observed only in extremely severe forms of hypothyroidism; hence, the limited sensitivity of the accelerometer technique likely contributed to decreasing the ability of estimating small differences in EE.…”
Section: Clinical Correlates Of Thyroid Disorders On Eementioning
confidence: 99%